Progress in Lean Manufacturing (Management and Industrial Engineering,, 2018)
This book provides some recent research advances in the field of lean manufacturing. Its content is of interest to students in management and production engineering. Topics covered include Just in Time (JIT), Kaizen activities and Critical Metrics. The chapters are written by worldwide well-known experts in the field.